The Influence Of Risk Based Capital, Investment Returns, and Operational Costs, On the Surplus Underwriting Of Islamic Insurance Companies at the 2014-2018 Period - Nita Yolanda Oktavia Fusen; Heraeni Tanuatmodjo; Aneu Cakhyaneu (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to see the overview and influence of risk based capital, investment returns, and operational costs, on the surplus underwriting in Sharia general insurance companies in Indonesia period 2014-2018. Surplus underwriting over the past five years has been fluctuating and almost all sharia general insurance companies in Indonesia have decreased. This is due to the decline in performance and financial instruments in Sharia general insurance companies in Indonesia. The research methods used in this study are causality methods with a quantitative approach. The population in this research is the Sharia general insurance company registered with Otoritas Jasa Keuangan (OJK). The method used for sampling in research is by purposive sampling with the number of samples as many as eleven Sharia general insurance companies in Indonesia for 5 years of research. The data used is secondary data. The statistical analysis technique used in this study was the analysis of a regression of data panels using the Eviews 9 application. The dependent variables in this study are surplus underwriting and independent variables in this research are risk based capital, investment returns, and operational costs. The results showed that risk based capital positively affect the surplus underwriting, investment returns positively affect the surplus underwritimg and operational cost positively affect the surplus underwriting